The Seemingness of the Perpetual Timeness of an Illusive ’Always’ - Papandritsa, Artemi (Conatus - Journal of Philosophy, 2018)
If philosophy is defined as the process of desiring to know, that is, as a methodical and systematic endeavor that seeks true reality, the question about “always” necessarily arises. The concept of “always” is indicative of eternal duration that, nevertheless, disappears as the time of its utterance passes by. In this paper I will first discuss truth and eternity as a necessary contract that is dependent on the ability to perceive any contract as something that leads rational agents to accept a true situation that corresponds to reality.